The value of noncoronary atherosclerosis for identifying coronary artery disease: results of the Leipzig LIFE Heart Study - Weissgerber, Alexander; Scholz, Markus; Teren, Andrej; Sandri, Marcus; Teupser, Daniel; Gielen, Stephan; Thiery, Joachim; Schuler, Gerhard; Beutner, Frank (Clinical research in cardiology, 2016)
Background Despite the widespread use of noninvasive testing prior to invasive coronary diagnostic the diagnostic yield of elective coronary angiography has been reported low in subjects with suspected obstructive CAD. Objective To determine the predictive value of noncoronary atherosclerosis (NCA) in subjects with suspected stable coronary artery disease (CAD) intended to invasive coronary angiography. Methods Ultrasound-based assessment of carotid artery plaque (CAP), carotid intima-media thickness (CIMT) and ankle-brachial index (ABI) was performed in 2216 subjects with suspected CAD prior to coronary angiography. Logistic regression and c-statistics were used to analyze the diagnostic value of NCA for the presence of obstructive CAD and the intention to revascularization. Results Percentage of positive results of elective coronary angiography was low but comparable to other studies (41 % obstructive CAD). We identified 1323 subjects (60 %) with NCA, most of them were characterized by CAP (93 %). CAP independently predicted obstructive CAD in addition to traditional risk factors and clinical factors while CIMT and ABI failed to improve the prediction. The presence of NCA and typical angina were the strongest predictors for obstructive CAD (OR 4.0 and 2.4, respectively). A large subgroup of patients ( n = 703, 32 %) with atypical clinical presentation and lack of NCA revealed a low indication for revascularization <15 % indicating a large proportion of subjects with non-obstructive CAD in this subgroup. Conclusion The evaluation of noncoronary atherosclerosis has the potential to impact clinical decision making and to direct subsequent diagnostic procedures in subjects with suspected coronary artery disease. Clinical trial registration NCT00497887.